Advances in mathematical and computational modeling of engineering systems - Awasthi, M. K. (ed.); Verma, M. (ed.); Ram, M. (ed.) (Boca Raton CRC Press, 2023)
"The text focuses on the recent research developments in the mathematical modeling and scientific computing of biological and engineering systems. It will serve as an ideal reference text for senior undergraduate, graduate students, and researchers in diverse fields including computer engineering, electrical engineering, mathematics, and fluid dynamics"--
Keywords: Systems engineering -- Mathematics; Engineering models; Biological systems -- Mathematical models